2018
DOI: 10.1111/jsbm.12442
|View full text |Cite
|
Sign up to set email alerts
|

Public Procurement and Small Businesses: Estranged or Engaged?

Abstract: How do “under‐represented” business owners engage with public procurement opportunities? Extant studies tend to offer prescriptions rather than theoretically guided responses to this question despite the importance of public procurement as a tool for economic development. Drawing on Edwards et al.'s (2006) institutionalist framework on small firm behavior, this paper examined the complex, subtle, interplay of structural factors and internal resources in shaping small firms' strategic choices and identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Regarding interfunctional coordination, our results suggest that a general discussion about public sector trends may reduce the willingness to bid. An explanation for this could be that some SMEs perceive the public procurement process as complex with stringent requirements (Woldesenbet and Worthington, 2019). If a firm lacks relevant information and experiential knowledge, the notion of the public sector being a cumbersome and hard-to-please customer may prevail in conversation (e.g., Loader, 2015), and consequently, constitute a barrier against bidding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding interfunctional coordination, our results suggest that a general discussion about public sector trends may reduce the willingness to bid. An explanation for this could be that some SMEs perceive the public procurement process as complex with stringent requirements (Woldesenbet and Worthington, 2019). If a firm lacks relevant information and experiential knowledge, the notion of the public sector being a cumbersome and hard-to-please customer may prevail in conversation (e.g., Loader, 2015), and consequently, constitute a barrier against bidding.…”
Section: Discussionmentioning
confidence: 99%
“…This could help them overcome the barrier of the ignorance of SMEs concerning the opportunities or procedures involved in public procurement (e.g., Loader, 2015). For example, Woldesenbet and Worthington (2019) found that having knowledge of the public sector helps small businesses to identify the opportunities available to them and to align and integrate resources and capabilities so that these opportunities can be realized as actual business transactions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, most research in procurement strategies has emphasised that there is a significant relationship between procurement strategies and social-economic growth of construction SMEs (Woldesenbet and Worthington, 2019; Patrucco et al , 2019; Windapo et al , 2019; Awuzie and McDermott, 2019; Yu et al , 2019; Da Costa and Da Motta, 2019). Naoum and Egbu (2015) observed that the integrated procurement strategy is useful in obtaining a higher market share and higher turnover.…”
Section: Research Background and Frameworkmentioning
confidence: 99%
“…In the public procurement policy landscape, tendering remains highly problematic for SMEs and the ongoing appearance of the so-called “SME-friendly” policies towards combating problems faced in tendering justifies this. In fact, according to Ancarani et al (2019), Woldesenbet and Worthington (2019) and Windapo et al (2019), the very existence of the “SME-friendly” policies is the cause of the failing market for SMEs. According to Flynn et al (2013) and Windapo et al (2019), the failure of construction SMEs in public procurement is attributable to the assumption of homogeneity across the SME population, and it is hindering the growth of SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Worthington, 2018) and experience in dealing with the public sector. The structure of the procurement process is perceived as complex (Glover, 2008;Woldesenbet & Worthington, 2018), beginning with the possibility of getting to hear of the call, which is reported as being difficult to obtain for SMEs which lack previous contracts with the public agency (European Commission, 2005). Easing SMEs' access can be obtained by the streamlining of bureaucratic procedures and the provision of information (GHK, 2010), for instance using national portals that allow public agencies to advertise tender opportunities and of streamlined pre-qualifications for use by SMEs (European Commission, 2005).…”
Section: Ppi and Smesmentioning
confidence: 99%